Working together for more equitable water sharing solutions - International Water Management Institute; WorldFish (International Water Management Institute, 2024)
A new video from the CGIAR Initiatives on Asian Mega-Deltas and Aquatic Foods documents work to support Cambodia to delegate the management of water, land, agriculture, fisheries, and the environment to the district level.